THE DEVELOPMENT OF AI AND ITS IMPACT TO OUR LIFE (Modern education and development, 2024)
This article examines the development of Artificial Intelligence (AI) and its profound impact on various aspects of human life. Tracing the evolution of AI from its early conceptual stages to the advanced machine learning and deep learning systems of today, the article explores how AI is transforming industries such as healthcare, finance, education, and transportation. The article discusses the benefits of AI, including increased efficiency, personalized services, and innovations in problem-solving. At the same time, it addresses the challenges and ethical concerns associated with AI, such as job displacement, privacy issues, and the potential for biased decision-making. By analyzing both the opportunities and risks presented by AI, this article provides a comprehensive overview of how this technology is reshaping society and offers insights into its future potential and implications for humanity.